Statistics for machine learning : Techniques for exploring supervised, unsupervised, and reinforcement learning modules with Python and R - Bangeti, Pratap (Packt, 2017)
Complex statistics in machine learning worry a lot of developers. Developing an accurate understanding of statistics will help you build robust machine learning models that are optimized for a given problem statement.